The role of MHD in causing impurity peaking in JET hybrid plasmas. (27th April 2016) - Hender, T.C.; Buratti, P.; Casson, F.J.; Alper, B.; Baranov, Yu. F.; Baruzzo, M.; Challis, C.D.; Koechl, F.; Lawson, K.D.; Marchetto, C.; Nave, M.F.F.; Pütterich, T.; et al.
Abstract: In hybrid plasma operation in JET with its ITER-like wall (JET-ILW) it is found that n   >  1 tearing activity can significantly enhance the rate of on-axis peaking of high- Z impurities, which in turn significantly degrades discharge performance. Core n   =  1 instabilities can be beneficial in removing impurities from the plasma core (e.g. sawteeth or fishbones), but can conversely also degrade core confinement (particularly in combination with simultaneous n   =  3 activity). The nature of magnetohydrodynamic instabilities in JET hybrid discharges, with both its previous carbon wall and subsequent JET-ILW, is surveyed statistically and the character of the instabilities is examined. Possible qualitative models for how the n   >  1 islands can enhance the on-axis impurity transport accumulation processes are presented.